Alterations in the pulmonary function tests of inflammatory bowel diseases - Fehmi ATEŞ; Melih KARINCAOĞLU; Süleyman Savaş HACIEVLİYAGİL and Mehmet YALNIZ and Yüksel SEÇKİN (Turkish Journal of Gastroenterology, 2019)
-